Onomatopoeia: When Sound Is Seen - Deny Tri Ardianto; Sayid Mataram; Anugrah Irfan Ismail; Arif Ranu Wicaksono (Mudra Jurnal Seni Budaya, 2023)
Phonogram is a visual element in comics that represents the existence of sound. Together with picture elements, they both create a construction that is governed by a narrative. As a manifestation of sound, phonogram’s existence also delivers a message in the form of signs. By using a semiotic approach, this study seeks to identify the nature of the phonogram, its function, and the way it is produced and perceived. Symbolic messages are created to dramatize comics. Because of phonogram’s nature that imitates stereotypes in the real world, comic artists lead the reader to agree on the false reality presented in comic works. Phonogram’s creation requires two step interpretations, namely interpretation of sound and interpretation of visualization. The form of expression on the phonogram is not universal, because it refers to certain cultural stereotypes.